Characteristics of Children With Invasive Pneumococcal Disease After the Introduction of the 13-valent Pneumococcal Conjugate Vaccine in England and Wales, 2010–2016. Issue 7 (July 2018) - Makwana, Ashley; Sheppard, Carmen; Borrow, Ray; Fry, Norman; Andrews, Nick J.; Ladhani, Shamez N.
Abstract : Background: In England and Wales, replacement of childhood 7-valent pneumococcal conjugate vaccine (PCV7) with a 13-valent vaccine (PCV13) in 2010 was associated with a significant reduction in PCV13-serotype invasive pneumococcal disease (IPD), with a small increase in IPD due to non-vaccine serotypes. Here, we describe the clinical presentation, comorbidity prevalence, serotype distribution and outcomes of childhood IPD during the first 6 years after PCV13 introduction. Methods: Public Health England conducts enhanced IPD surveillance in England and Wales, with detailed information requested from general practitioners for all cases in children <5 years of age. Invasive isolates are routinely serotyped at the Public Health England reference laboratory. Results: From April 2010 to March 2016, 1280 IPD episodes were confirmed in 1255 children 3–59 months of age; 84.3% (1059/1255) isolates were serotyped. Clinical presentation with meningitis was most prevalent in 3- to 11-month olds (45.8%, 209/456) and lower respiratory tract infection in 24- to 59-month olds (46.7%, 133/285). Overall, 259 (20.6%) children had 292 comorbidities, particularly immunosuppression (31.6%, 92/292). Twenty-one children (1.8%) had recurrent IPD. The case fatality rate was 5.1% (64/1255; 95% confidence interval [CI]: 3.9%–6.5%) and independently associated with meningitis (aOR 3.53; 95% CI: 1.62–7.70) and presence of comorbidity (aOR, 2.41; 95% CI: 1.25–4.64). In 2015/2016, PCV13 serotypes were responsible for 10.8% (25/232) of serotyped cases; the most prevalent non-PCV13 serotypes were 12F (18%), 10A (12%), 23B (10%), 33F (10%), 15B/C (10%) and 8 (8%). Conclusions: Most childhood IPD cases are now due to non-PCV13 serotypes. A higher proportion of children with IPD have underlying comorbidity, but, reassuringly, the risk of recurrent IPD or death remains low. Abstract : Supplemental Digital Content is available in the text.